ANALYSIS OF GUIDE VANE GEOMETRY TOWARDS PERFORMANCE OF FRANCIS TURBINE 63 MW ON BAKARU HYDRO POWER PLANT - Calvin Gunawan, Agustinus
Bakaru Hydro Power Plant (HPP) is a power plant that uses two units of Francis Turbines to generate 126 MW worth of electricity. Francis turbines are composed of several main components such as runner, guide vanes, stay vanes, spiral case, and draft tube. Bakaru HPP operates on an area that has large amount of sediment on its water which shorten the lives of the components. One of the components that is affected greatly is guide vanes. Failure on a guide vane means that the components cannot be repaired therefore need to be replaced. Currently, officers in Bakaru HPP is using imported products from Japan for those components. The high frequency of guide vanes replacement acts as a cause of high maintenance cost. As an effort to reduce maintenance cost and to increase the quality of local products, a reverse engineering process will be done on the existing guide vane. Solution for the problem will be achieved through modelling the airfoil geometry of the existing guide vane, redesigning Francis turbine 63 MW, and CFD simulation of Francis turbine using various airfoil geometries under several guide vanes opening angle. The simulation results of the redesigned Francis Turbine can represent the actual Francis Turbine on Bakaru HPP, as the output power does not differ more than 5%. The simulation results and analysis of Francis turbine with various airfoil geometries shows that the NACA 2419 airfoil profile has higher efficiency in most of the operating regions, therefore more compatible to be applied on Bakaru HPP.